2013
DOI: 10.1038/eye.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal neovascularization in 36 eyes of children and adolescents

Abstract: Purpose To describe the clinical features and outcomes among eyes with choroidal neovascularization (CNV) in children and adolescents. Methods A total of 36 eyes of 27 patients o18 years of age diagnosed with CNV between January 1978 and December 2008 were retrospectively reviewed. CNV was clinically diagnosed in all patients and its presence was confirmed by fundus fluorescein angiography (FFA). A total of 19 eyes underwent treatment. Anatomical outcome was evaluated as regressed/ persistent/recurrent CNV. Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 80 publications
0
42
0
5
Order By: Relevance
“…Previous papers report spontaneous regression in 58%26 and 41.7%2 of the eyes. A characteristic finding that may be predictive of regression is a pigmented ring or encapsulation around the lesion 27.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous papers report spontaneous regression in 58%26 and 41.7%2 of the eyes. A characteristic finding that may be predictive of regression is a pigmented ring or encapsulation around the lesion 27.…”
Section: Discussionmentioning
confidence: 90%
“…The disorder is rare with an annual incidence in the UK for those aged 16 and under of 0.21 per 100 000. Two retrospective studies of CNV in children younger than 18 years2 9 reported opposing gender preponderance, with Barth et al 9 reporting a strong female predominance (80%), in contrast to Rishi et al, 2 who described a higher male preponderance (63%). This result may be due to the different ethnic background and access to healthcare facilities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The recent establishment of intravitreal antiangiogenic treatment for CNV secondary to exudative age-related macular degeneration (AMD) has led to increasing reports of anti-VEGF (vascular endothelial growth factor) therapy for CNV of other causes than AMD and in younger populations [17][18][19]. However, due to the rarity of PIC-related CNV no evidence-based treatment protocol exists [1,13].…”
Section: Introductionmentioning
confidence: 98%
“…5 months on average (SD 5.5, range[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Although the eyes treated by ranibizumab (n = 2) had a slightly better functional outcome (DBCVA ?1.5 lines) compared to the eyes injected with bevacizumab (n = 13, DBCVA ?0.77 lines), no conclusion can be drawn about the superiority of one of the anti-VEGF agents because of the low sample sizes.Visual acuity, refraction and functional outcomeThe refractive error was recorded in 13 (81%) eyes with a mean spherical equivalent of -4.3 dioptres (D) (SD 3.1 D, range -7.0 to 0.5 D).…”
mentioning
confidence: 99%